International human rights law : cases, materials, commentary - Schutter, Olivier de (Cambridge : Cambridge University Press, 2019)
International human rights law has expanded remarkably since the 1990s. It is therefore more important than ever to identify, beyond specific controversies, its deeper structure and the general pattern of evolution. Moreover, it has a logic of its own: though part of international law, it borrows many of its principles from domestic constitutional law. This leading textbook meets both challenges. It has been significantly updated for the new third edition, introducing sections on subjects including business and human rights, amongst other key areas. Features include forty new cases from various jurisdictions or expert bodies, and figures offering visual descriptions of the procedures discussed in the text. The 'questions for discussion' have also been systematically updated. The text retains its student-friendly design, and the features which made the previous editions so engaging and accessible remain. This popular textbook continues to be an essential tool for all students of human rights law.
The rise of international human rights -- State responsibility and 'jurisdiction' -- 'Respecting human rights : avoiding interference -- Protecting human rights : regulating private actors introduction -- Fulfilling human rights : progressive realization -- Derogations in time of public emergency -- The prohibition of discrimination -- Ensuring compliance with international human rights Law : the role of national authorities -- The United Nations human rights treaties system introduction -- The United Nations charter-based monitoring of human rights -- Regional mechanisms of protection.
Title from publisher's bibliographic system (viewed on 17 Jul 2020).
Keywords: elektronické knihy; electronic books; Human rights; International law and human rights